Islam Rahmatan Lil Alamin Paradigm and Its Implications for Strengthening Student Profiles in Nusantara - Nurdin, Arbain; Hendra, Hendra; Tobroni, Tobroni; Khozin, Khozin (FENOMENA, 2023)
The purpose of this research is to describe the concept of Islam rahmatan lil’alamin perspective of Ulama and to analyze its implications for strengthening students profile in Nusantara. This study was conducted using a library research method, and the research data sources were diverse articles and research findings on the paradigm of Islam rahmatan lil’alamin and its implications. The research findings revealed that Ulama have provided their views on this matter, such as KH. Hazim Muzadi, who proposed three approaches to promote Islam Islam rahmatan lil’alamin, KH. Achmad Siddiq, who developed the concept of ukhuwah trilogy, and KH. Achmad Dahlan, who emphasized values in his preaching method. The implications of these findings provide support for shaping the profiles of students in Nusantara by designing programs and activities that offer opportunities for students to develop and actualize the values of rahmatan lil’alamin, both within the school environment and in society